Penerapan Perencanaan Pajak Penghasilan pada Fa Trico Paint Factory - Ariyanto, Stefanus; Hartanto, Andrew (Binus Business Review, 2011)
The most important parts of government income comes from taxes, especially income taxes. The different point of view arises between government and tax payer. While the government try to increase the tax income, the taxpayers always intend to minimize their tax burden by implementing tax management/plannning. This paper is a case study in FA Trico Paint Factory (FA TPF) that try to reperforming companyâs income tax return preparation with the main purpose to minimize company tax burden, while it is still comply with tax regulations in Indonesia. This approach could be an alternative for the company to restate itâs annual income tax return, to avoic fines and charges for not comply with the regulations, and minimize itâs income tax expense by approximately 10% per year.Â